Grain-based Foods: Processing, Properties, and Heath Attributes - Emanuele Zannini (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The Special Issue aims to provide a complete exploration of the scientific principles related to processing, fermentation/malting, and nutrition of cereal grains. It also describes their physical and chemical characteristics and explains how these properties relate to health and nutritional value of the final grain-based products. Indeed, while grains remain the world's largest food yield-with more than 2.4 billion metric tons produced annually-consumer demands are on the rise for grain products sustainable from an environmental, social and economic viewpoint, in order to meet the growing demand for healthy and nutritious foods.